Please need help on 2 math questions

13. Divide the rational expressions.


(7y-1)/(y2-36)÷(1-7y)/(y+6)


2. Add or subtract as indicated. Write the answer in descending order.

(3n^4 + 1) + (–8n^4 + 3) – (–8n^4 + 2)


A. –13n^4 + 6


B. 3n^4 + 6


C. 3n^4 + 2


D. 19n^4 – 4



Respuesta :

Question 1:

For this case we have the following expression:

[tex]\frac {\frac {y-1} {y ^ 2-36}} {\frac {1-7y} {y + 6}} =\\\frac {(7y-1) (y + 6)} {(y ^ 2-36) (1-7y)} =[/tex]

We have to:

[tex]y ^ 2-36 = (y + 6) (y-6)[/tex]

Rewriting:

[tex]\frac {(7y-1) (y + 6)} {(y + 6) (y-6) (1-7y)} =\\\frac {7y-1} {(y-6) (1-7y)} =[/tex]

We take common factor "-" in the denominator:

[tex]\frac {7y-1} {(y-6) * - (- 1 + 7y)} =\\\frac {7y-1} {- (y-6) * (7y-1)} =\\- \frac {1} {(y-6)}[/tex]

ANswer:

[tex]- \frac {1} {(y-6)}[/tex]

Question 2:

For this case we must simplify the following expression:

[tex](3n ^ 4 + 1) + (- 8n ^ 4 + 3) - (- 8n ^ 4 + 2) =[/tex]

We eliminate parentheses keeping in mind that:

[tex]+ * - = -\\- * - = +\\3n ^ 4 + 1-8n ^ 4 + 3 + 8n ^ 4-2 =[/tex]

We add similar terms:

[tex]3n ^ 4-8n ^ 4 + 8n ^ 4 + 1 + 3-2 =\\3n ^ 4 + 2[/tex]

Answer:

[tex]3n ^ 4 + 2[/tex]